Member - Nicolaou, Anna (My University, 2026)
1st EUt+ Conference on Languages – Inter/Multiculturalism in a Post-Colonial Era: Languages and European Values (EUtLC2024), Darmstadt University of Applied Sciences, Darmstadt, Germany, January 2024. (Contributed to the editorial and peer-review process for conference proceedings)